Improvement and Mitigation of Kerr Effects on Multichannel ‎Communication Systems Using Efficient Optical Method (Journal of University of Babylon for Engineering Sciences, 2023)
This paper studies the generation of an optical mitigation method for compensation of distortions in long distance fiber optic transmission caused by chromatic dispersion and the nonlinear Kerr effect in multi-channel systems. A hybrid new method known as Optical Phase Conjugation (OPC) based highly nonlinear fiber with Raman amplifier is used as part of the process of improving the performance of communication systems with an 800 km standard single mode fiber link Single Polarization Quadrature Amplitude Modulation (SP-QAM) signaling. This work presents two scenarios in which backward Raman amplification is employed in conjunction with OPC to improve the performance of an optical link of 1.728 Tb/s over sixteen channels with a channel spacing of 50 GHz. In this study, through the use of multiple OPC, the performance of dense wavelength division multiplexing (DWDM) transmission systems with 16 ×108 Gbps 8-QAM channels can be significantly improved over that of systems with either a mid-span optical phase conjugation or no optical phase conjugation. The strategy of using multiple OPCs is effective over a variety of transmission links. The nonlinear threshold in the proposed transmission system was enhanced by 4 dB when employing multiple OPCs, compared to the case with no OPC, and by 2 dB when using a mid-span OPC. The simulation results show that compared to the scenario without employing the compensation approach, the Q-factor, Bit Error Rate (BER) performance, and total length of the transmission link are all improved by utilizing this optical method of nonlinearity compensation.